Scopes and challenges Of sustainable procurement In Public Works Department (PWD), Bangladesh - Hoque, Md. Mosta Gausul (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.